Guyana : from economic recovery to sustained growth (World Bank WashingtonUS, 1993)
Reviews the current macroeconomic condition of the country, as well as recent developments and issues in important sectors. Part I deals with the broader issues of macroeconomic management and resources allocation. Part II examines in more depth issues in certain key sectors, and the role of public policy in sustaining the recovery effort. Includes private sector and industrial development, and the role of the state in setting incentives for private investment.
DC